Relationship between leisure-time physical activity and depressive symptoms under different levels of dietary inflammatory index - You, Yanwei; Chen, Yuquan; Yin, Jiahui; Zhang, Zheng; Zhang, Kening; Zhou, Jing; Jin, Shuai (Frontiers in Nutrition, 2022)
Depressive symptoms are major public health problems. Leisure-time Physical activity (LPA) and dietary inflammatory preference are emerging factors that tends to affect the mental health status. There is limited evidence regarding the joint influence of LPA and dietary status on the prevalence of depression. This study was a cross-sectional study, which used a nationwide represented sample from the National Health and Nutrition Examination Survey (NHANES) to assess the relationship among LPA, diet status and depression. Depression and LPA status was reported by the 9-item Patient Health Questionnaire (PHQ-9) and Physical Activity Questionnaire (PAQ), respectively. To assess dietary inflammatory preferences, dietary inflammatory index (DII) was applied based on a 24-h dietary recall interview. A total of 11,078 subjects was included in this study and weighted participants were 89,682,020. Weighted multivariable linear regression showed that DII was negatively associated with LPA after full adjustment, with β (95% CI): -0.487 (-0.647, -0.327). Weighted multivariable logistic regression showed that LPA was significantly associated with depressive symptoms after full adjustment, with odds ratios OR (95% CIs): 0.986 (0.977,0.995). By DII stratification analysis, this phenomenon was also existed in groups with anti-inflammatory diet. Mediation effect analysis was further performed, which showed that DII significantly mediating the association between LPA and depression with proportion mediated as 3.94%. Our findings indicated the mediating role of DII in the association between LPA condition and incident depression. More well-designed studies are still needed to validate the causal relationship.